Thomas & friends. Tale of the brave [videorecording (DVD)]. - Silvestri, Rob; Awdry, W. (Universal Studios Home Entertainment : Hit Entertainment, 2014)
After a monstrous storm on the Island of Sodor, a landslide unearths some very unusual footprints. Thomas and Percy are eager to find out what could have made these marks but obstacles and danger seem to appear around every bend in the track. With the help of new friends, a little digging, and a heap of courage, they discover the surprising answer and, along the way, uncover the true meaning of bravery